2023
DOI: 10.1007/s10755-023-09652-x
|View full text |Cite
|
Sign up to set email alerts
|

‘Professor Moms’ & ‘Hidden Service’ in Pandemic Times: Students Report Women Faculty more Supportive & Accommodating amid U.S. COVID Crisis Onset

Abstract: Emerging data suggests the COVID-19 crisis exacerbated preexisting, long-documented gender inequities among U.S. faculty in higher education. During the initial Spring 2020 ‘lockdown’ in the U.S., 80 students conveyed their experiences with faculty across 362 courses. We evaluated whether students’ reports of faculty supportiveness, accommodations granted, and pandemic-impacted, anticipated grade outcomes differed according to faculty gender via mixed linear models (data on 362 courses were nested within 80 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…The study reports that such norms translated into a great burden of care for women towards peers and students, ultimately resulting in a heavy impact on their own productivity (European Commission, 2023;Staniscuaski et al, 2021). Of course, a closer look will show us that such effects were higher for racialised women and women belonging to one or more marginalised communities (Docka-Filipek et al, 2023;Staniscuaski et al, 2021). In this sense, the pandemic brought to the forefront-and arguably heightenedexisting inequalities in the day-to-day operations of academia, and specifically teaching and service, which are already disproportionately carried by women (European Commission, 2023).…”
Section: The Gendered Dimension Of Academic Citizenshipmentioning
confidence: 99%
See 1 more Smart Citation
“…The study reports that such norms translated into a great burden of care for women towards peers and students, ultimately resulting in a heavy impact on their own productivity (European Commission, 2023;Staniscuaski et al, 2021). Of course, a closer look will show us that such effects were higher for racialised women and women belonging to one or more marginalised communities (Docka-Filipek et al, 2023;Staniscuaski et al, 2021). In this sense, the pandemic brought to the forefront-and arguably heightenedexisting inequalities in the day-to-day operations of academia, and specifically teaching and service, which are already disproportionately carried by women (European Commission, 2023).…”
Section: The Gendered Dimension Of Academic Citizenshipmentioning
confidence: 99%
“…For instance, throughout the past few decades, studies have shown that women tend to engage in such activities at a substantially higher rate than their male counterparts (Beauregard, 2012;Diefendorff et al, 2002;Eagly & Crowley, 1986;Guarino & Borden, 2017), often assuming the role of the 'caretaker' or 'professor mom' (cf. Docka-Filipek et al, 2023). As is to be expected, this leaves some women with much less time for research and may end up being potentially harmful for their career, personal development, and wellbeing-especially when academic career trajectories are not level or equitable to begin with.…”
Section: Introductionmentioning
confidence: 99%
“…Rather, departments and universities should provide the necessary support and infrastructure to facilitate such courses to those who choose to provide such a modality, without the amount of physical and technical labor required becoming a deterrent. This is especially important considering that often, such labor disproportionately falls upon professors and instructors with marginalized identities, as they shoulder higher emotional and technical burdens to accommodate student needs in comparison to their more privileged colleagues [28], [29]. In future extensions of this work, we intend to examine such instructor labors to elucidate this point further.…”
Section: Discussionmentioning
confidence: 99%